Pericyte Chemomechanics and the Angiogenic Switch: Insights Into the Pathogenesis of Proliferative Diabetic Retinopathy? - Durham, Jennifer T. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE. To establish the regulatory roles that pericytes have in coordinating retinal endothelial cell (EC) growth and angiogenic potential. METHODS. Pericytes were derived from donor diabetic (DHuRP) or normal (NHuRP) human retinae, and characterized using vascular markers, coculture, contraction, morphogenesis, and proliferation assays. To investigate capillary “cross-talk,” pericyte-endothelial coculture growth, and connexin-43 (Cx43) expression assays were performed. Paracrine effects were examined via treating EC with pericyte-derived conditioned media (CM) in proliferation, angiogenesis, and angiocrine assays. The effects of sphingosine 1-phosphate (S1P) were assessed using receptor antagonists. RESULTS. The DHuRP exhibit unique proliferative and morphologic properties, reflecting distinctive cytoskeletal and isoactin expression patterns. Unlike NHuRP, DHuRP are unable to sustain EC growth arrest in coculture and display reduced Cx43 expression. Further, CM from DHuRP (DPCM) markedly stimulates EC proliferation and tube formation. Treatment with S1P receptor antagonists mitigates DPCM growth-promotion in EC and S1P-mediated pericyte contraction. Angiocrine assays on normal and diabetic pericyte secretomes reveal factors involved in angiogenic control, inflammation, and metabolism. CONCLUSIONS. Effects from the diabetic microenvironment appear sustainable in cell culture: pericytes derived from diabetic donor eyes seemingly possess a “metabolic memory” in vitro, which may be linked to original donor health status. Diabetes- and pericyte-dependent effects on EC growth and angiogenesis may reflect alterations in bioactive lipid, angiocrine, and chemomechanical signaling. Altogether, our results suggest that diabetes alters pericyte contractile phenotype and cytoskeletal signaling, which ultimately may serve as a key, initiating event required for retinal endothelial reproliferation, angiogenic activation, and the pathological neovascularization accompanying proliferative diabetic retinopathy.